Կատարենք մեր ստացած բոլոր բանաձևերի ամփոփում


\[y=c \quad y'=0\]

\[y=x \quad y'=1\]

\[y=x^μ \quad y'=μx^{μ-1}\]

\[y=\frac 1x \quad y'=-\frac{1}{x^2}\]

\[y=\sqrt x \quad y'=\frac{1}{2 \sqrt x}\]

\[y=a^x \quad y'=a^x ln a\]

\[y=e^x \quad y'=e^x\]

\[y=log_a x \quad y'=\frac{log_a e}{x}\]

\[y=ln x \quad y'=\frac 1x\]

\[y=sin x \quad y'=cos x\]

\[y=cos x \quad y'=-sin x\]

\[y=tg x \quad y'=sec^2 x = \frac 1{cos^2 x}\]

\[y=ctg x \quad y'=-csc^2 x =-\frac 1{sin^2 x}\]

\[y=arcsin x \quad y'=\frac{1}{\sqrt{1-x^2}}\]

\[y=arccos x \quad y'=-\frac{1}{\sqrt{1-x^2}}\]

\[y=arctg x \quad y'=\frac{1}{1+x^2}\]

\[y=arcctg x \quad y'=-\frac{1}{1+x^2}\]

Կիսվեք ընկերների հետ

 

Օգտագործվում են uKit ծառայություններ